Analisis Akad Wakalah Bil Ujrah Pada Jasa Titip Beli Makanan di Asrama Putri STAI As-Sunnah Deli Serdang : Persepektif Syariat dan Implementasi Praktis: Perspektif Syariat dan Implementasi Praktis - Afifah, Afini Rizkiya; Fachri Rinaldy; Sindi Tifani (SALSABIL : Jurnal Syariah dan Hukum Ekonomi, 2025)
In Islam, the concept of Wakalah refers to assigning a task to someone to perform an action on behalf of the task giver. The purpose of this writing is to find out which wakalah contracts are permissible and which wakalah contracts are not, so that a Muslim can be careful and avoid elements of usury and gharar. As well as a reference in appliying wakalah principle related to finance and business, such a buying and selling, and investment management, managging asseta and others properly and in accordance with sharia law. The method used is qualitative analysis using the approach of fiqh books, ulama fatwas, and contemporary trade regulations. The research results show that the practice of entrusting services can be categorized as a form of wakalah bil ujrah (wakalah with compensation) as long as it meets sharia principles and avoids gharar and usury, both of which are prohibited.